PRESERVATION OF ARCHAIC WORDS IN MODERN LANGUAGE - Eshmurodova Dilfuza Bekzod kizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: This paper examines the role of archaic words in modern language, the reasons for their preservation, and their functional and stylistic significance. Special attention is given to their cultural and communicative value in contemporary discourse.